#TITLE_ALTERNATIVE# - Fadli (NIM 129 02 007), Mohammad
Abstract: A method to produce tidal current field using tidal current prediction based on tidal current components derived from hidrodynamic model was applied in Malacca Strait. Tidal current components that are derived from current field resulted from hidrodynamic model are produced using Admiralty Method. Hidrodynamic simulation results (elevation and current field) was verified with tidal elevation data from DISHIDROS and tidal current data from BPPT buoy. Current field resulted from prediction using tidal current components show a good similarity with the result of model simulation. The time that needed to produced tidal current field from prediction using tidal curent components are thirty time faster than running model.